CLINICAL AND DEMOGRAPHIC PROFILE OF MEN 1 AND MEN 2A: A 10 YEARS’ EXPERIENCE - Chin, Yik Hin; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Multiple endocrine neoplasia (MEN) syndromes are rare genetic disorders causing tumours in endocrine glands, with MEN 1 primarily affecting the parathyroid, pancreas, and pituitary, while MEN 2A is characterized by parathyroid tumour, medullary thyroid carcinoma (MTC) and pheochromocytoma. METHODOLOGY A retrospective cross-sectional study was conducted at Institut Endokrin Hospital Putrajaya. Electronic medical records of patients who attended Endocrinology or combined surgical clinic between 1st January 2015 till 31st March 2025 were reviewed. Descriptive and statistical analyses for MEN 1 and MEN 2A patients were performed using SPSS version 25. RESULT The cohort comprised 16 patients with MEN syndromes—10 with MEN 1 and 6 with MEN 2A. There was a balanced gender distribution (56% male, 44% female), with an age range of 19 to 70 years (mean: 48 years). Patients with MEN 1 were slightly older (mean age: 49 years) compared to those with MEN 2A (mean age: 44 years). In the MEN 1 population, all had parathyroid involvement (100%), with 60% exhibiting pancreatic tumors and 30% adrenal or pituitary lesions. Most underwent parathyroid (80%) and pancreatic (60%) surgeries. Only 20% had family members screened for MEN genes, suggesting that family screening rate is still low. In the MEN 2A population, all cases featured medullary thyroid carcinoma (MTC) and RET oncogene mutations, with 83% found to have parathyroid disease and 50% with pheochromocytoma. Thyroid surgery was done for all patients while 83% underwent parathyroidectomy as well. Half had access to family genetic screening, emphasizing the hereditary nature of MEN 2A. CONCLUSION Distinct profiles emerged from our cohort. Multiple endocrine neoplasia 1 is marked by parathyroid-pancreatic axis tumors, whereas MEN 2A is defined by MTC and RET mutations. A multidisciplinary approach, including genetic screening and tailored surgery, is critical for optimal outcomes. Genetic screening access for patient and family members can be improved to close the critical gaps in cascade testing for at-risk relatives.